The effects of a - tocopherol and verapamil on mucosal functions after gut ischemia / reperfusion* - Mahmut Can YAĞMURDUR,; Arif ÖZDEMİR,; Ahmet ÖZENÇ,; Kamer KILINÇ, (Turkish Journal of Gastroenterology, 2019)
-